Lamination - Papadopoulos, George (Glass handbooks., 2004)
This practical handbook covers the process of taking sheets of glass, decorating them by painting, sandblasting, cracking, shattering or etching, then covering them with another layer and fusing the layers together. Material, metal, paper etc can also be used as decoration between the layers. The process can be applied on a variety of scales, from very small (used for jewelery, etc) to large wall panels and room dividers. Since glass can be used along with a wide range of other materials there is great scope for mixed media projects.